The growth performance of Osphronemus goramy reared in saline water with electrical field exposure - Kukuh Nirmala; . Rasmawan (Jurnal Akuakultur Indonesia)
The aim of this study was to know the optimal salinity level on growth rates of giant gouramy Osphronemus goramy  reared in different salinity with electrical field exposure. Four different salinities tested were 0; 3; 6 and 9‰ with the electrical field exposure of 10 Volt. The experiment design was arranged in completely randoumizes design with four treatments and three replications. Stock density was 3 fish/l with mean initial total body length of 7.18±0.30 cm and initial body weight of 5.68±0.67 g. Result of study showed that the treatment of 3‰ shows the best growth performance with specific growth rates of 1.02±0.10% and growth of absolute length of 0.56±0.18 cm.